Enhancement human cytomegalovirus replication in a human lung fibroblast cell line by interleukin-8. - Murayama, T (1994)
We examined the effects of interleukin-8 (IL-8) on cytomegalovirus (CMV) replication in human fibroblasts. Exposure of fibroblasts to IL-8 augmented both infectious virus production and replication of CMV, with concomitant increases in the levels of both the transcript of the CMV pp71 genome and the synthesis of the CMV late antigen. We also found that CMV selectively induced transcripts of the IL-8 type 1 receptor in fibroblasts. These results suggest that IL-8 also contributes to inflammatory diseases by enhancing CMV replication and that CMV regulates its production through induction of IL-8 receptor.